Intervenções teórico-práticas com licenciandos em química por meio de problemas temáticos. - Silva, Édila Rosane Alves da (2020)
This work presents a didactic strategy developed in the initial teaching formation in Chemistry, through the articulation between the Methodology of Resolution of Problems and Thematic, which was called Thematic Problems. Thematic Problems encompass the approach of problem situations linked to thematic issues that require scientific knowledge for their reflection and subsequent resolution. The present research had as a guiding question: "How can the elaboration of Thematic Problems contribute to the initial formation of Chemistry teachers?". Seeking to answer this question, it was established as specific objectives to verify, how the Methodology of Resolution of Problems has been worked in the initial teaching formation in Chemistry, through the analysis in national and international journals; Elaborate and implement didactic activities for academics of the Chemistry Degree course, specifically in the class hours dedicated to Educational Practices; Propose the development, by academics, of sequences of activities that could be used in Basic Education; Analyze and evaluate the teaching materials produced by the graduates, both in technical-scientific and methodological terms, as well as their possible adaptation in Basic Education. Through bibliographic research, which covered the period from 2007 to 2018, 14 articles were examined among the 878 publications found. The analysis of these works allowed us to verify which the main theoretical references related to themes have been used in Higher Education, the nature of the problems developed, the curricular panorama, the pedagogical, formative and reflective aspects about the initial teacher education. In a later stage, the students answered a questionnaire in order to verify their conceptions about the educational practices already taken. Based on the analysis of these data, theoretical-practical interventions were developed to be developed with students from the 3rd semester of the Chemistry Degree course, from the Federal University of Santa Maria - UFSM, specifically in the classes hours aimed at the educational practices of the Quantitative Analytical Chemistry discipline Experimental. The implemented interventions were attended by 13 academics and took place in the first semester of 2019, totaling 31 hours between face-to-face and distance meetings. At first, the undergraduate students formulated problem situations based on thematic texts, which were called the Initial Essay. In another opportunity, Thematic Problems were produced, based on pre-established contents and, later, lesson plans were elaborated, containing the Thematic Problems, for an imminent transfer to Basic Education. In addition, academics answered questionnaires, at the beginning and end of the proposal, in order to verify their conceptions about the work done. The data obtained in this research were analyzed using the theoretical framework proposed for the Pedagogical Knowledge of the Content and the Likert Scale. The analysis of the data collection instruments allowed us to infer that the elaboration of the Thematic Problems contributed for the students to know other teaching methods, to take ownership of the ways of transposing the conceptual knowledge to the Basic Education, perceiving the relevance of the professional teaching activities in the basic training, as well as, the importance of developing activities that favor the adoption of scientific concepts associated with social demands.